THE RESULT OF RESEARCH AND DEVELOPMENT OF TRAINING MANAGEMENT MODEL OF ISLAMIC EDUCATION CONTAINING MULTICULTURALISM FOR SENIOR HIGH SCHOOL PAI TEACHERS IN PEMALANG REGENCY (Universitas Negeri Semarang, 2015)
This study aims to find out and develop goodfactual model, design, design model, hypothetical model and the final model of education and training of Islamic Religion Education (PAI) containing multiculturalism for PAI senior high school (SMA) teachers, including its planning, organizing, implementation, monitoring, and evaluation, as well as the needed follow-up assistance of post training program. Develop a model for training management modelcontaining multiculturalism for PAI teachers is important so they can improve their professional competence. The result of research anddevelopment shows that the existingfactual model of PAItraining for the teachers is still not effective and produces low competence. In response to that, the designed training model of PAI containing multiculturalism to enhance the professional competence of teachers PAI has beenempirically validated by a team of experts and practitioners and it can improve the competency of PAI teachers. The hypothetical model validation resulted from experts and practitioners through FGDs deserves to be applied to the trial I and II. The final model after FGD II is effective in a trial proven by practicality of training model that has compatibility with different types and target groups of the study. For MORA RI, it is suggested to always improve the professional competence of PAI teachers and uses the designed training model containing multiculturalism on an ongoing basis. The related stakeholders need to cooperate in developing a better research and development in creating abetter PAI training model.